Beyond prohibition: responses to illicit drugs in West Africa in an evolving policy context. Issue 2 (10th July 2020) - Nelson, Ediomo-Ubong; Obot, Isidore
Abstract : Purpose: The purpose of this paper is to discuss priorities for effective responses to illicit drugs in West Africa in a changing international policy environment. Design/methodology/approach: The paper analyzes published research, technical papers and reports on drug use and policy responses in West Africa and opines on priorities for drug policy in the region within the post-United Nations General Assembly Special Session (UNGASS) 2016 policy environment. Findings: Drug use and related harms continue to increase in West African countries despite efforts to reduce drug trafficking and use through legal prohibition. The UNGASS 2016 outcome document enables flexibility in policy interpretation and implementation, which provides an opportunity for governments to prioritize national needs in drug policy. West African countries should prioritize and support research and data collection, prevention, treatment and harm reduction and sustainable livelihoods. Originality/value: The paper emphasizes the need for West African countries to seize the opportunity created by the ineffectiveness and weakening of the prohibition regime as well as new treaty flexibility following UNGASS 2016 to reform drug policies to prioritize regional and national needs.